2012
DOI: 10.1038/bmt.2012.140
|View full text |Cite
|
Sign up to set email alerts
|

Alternative donor SCT for the treatment of MHC Class II deficiency

Abstract: MHC Class II deficiency is a rare primary immunodeficiency disease characterized by absent HLA Class II expression resulting in CD4 lymphopenia, lack of Ag-specific responses and recurrent infection. Without successful allogeneic SCT, most children succumb to infection within the first decade of life. To date, alternative donor transplants for this disorder have been inferior to SCT for other forms of combined immunodeficiency disease due to an increased incidence of graft rejection, GVHD and death from infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Renella et al, reported a 50% rate of GVHDs higher than grade I in 14 patients with MHC II deficiency that had undergone HSCT. 24 A study on 23 patients with MHC II deficiency reported a rate of about 50% (12/23) deaths one month to six years after HSCT, most of which happened immediately after the transplant due to severe GVHD or severe infections. 10 In comparison, seven out of 12 patients on supportive care who did not undergo HSCT were alive at the end of this study.…”
Section: Treatmentmentioning
confidence: 99%
“…Renella et al, reported a 50% rate of GVHDs higher than grade I in 14 patients with MHC II deficiency that had undergone HSCT. 24 A study on 23 patients with MHC II deficiency reported a rate of about 50% (12/23) deaths one month to six years after HSCT, most of which happened immediately after the transplant due to severe GVHD or severe infections. 10 In comparison, seven out of 12 patients on supportive care who did not undergo HSCT were alive at the end of this study.…”
Section: Treatmentmentioning
confidence: 99%
“…If no family donor is found, a search of the national or international unrelated donor registries should be undertaken. Parental haploidentical donors with newer methods of T-lymphocyte depletion have emerged as promising alternative donors while classic haploidentical HSCT with CD34+ selection have shown high rate of non-engraftment in historical series (13)(14)(15)(16). The use of myeloablative reduced-toxicity conditioning (RTC) is preferred in children with MHC class II deficiency as many patients have multiple chronic infections and organ damage at the time of HCT.…”
Section: Transplant Phasementioning
confidence: 99%
“…At the end of the study, 11 of 16 patients survived, with acute GVHD occurring in 6 of 16 patients and the decedents dying of GVHD or widespread fungal and viral infections. 10 As expression of MHC II on recipient antigen-presenting cells may be required for immune-mediated graft rejection following BMT, why patients with BLS are at higher risk for graft rejection is an intriguing question. This raises the likelihood that other factors besides immunemediated rejection are involved in the pathogenesis of engraftment failure.…”
mentioning
confidence: 99%
“…Alternatively, donor antigen-presenting cells could present donor antigens to recipient T-cells leading to graft rejection. Residual host immunity in MHCII deficiency is sufficient to cause rejection even with immunosuppression, seen in multiple reports of patients requiring retransplantation (3 of 30 patients, 6 2 of 6 patients, 7 3 of 16 patients, 10 2 of 15 patients 11 ). Another fundamental question is why patients with MHC II deficiency need HLA-matched donors, given that the recipient cells lack MHC II molecules and might therefore not mount an immune response.…”
mentioning
confidence: 99%